Rural schools as effective hubs for agricultural technology dissemination: experimental evidence from Tanzania and Uganda - Kpaka, H.M.; Assfaw Wossen, T.; Stein, D.; Mtunda, K.; Laizer, L.; Feleke, S.; Manyong, Victor (Oxford University Press, 2022)
Increasing agricultural productivity by promoting high-yielding and micronutrient-rich crop varieties has the potential to reduce poverty and malnutrition. However, getting these technologies into the hands of smallholders remains a challenge. This paper presents results from a randomised field experiment that uses rural primary schools as dissemination hubs for improved orange-fleshed sweet potato (OFSP) vines and nutrition information in rural Tanzania and Uganda. Two years after the initial vine distribution, we find that households in treatment villages are 21 percentage points more likely to report growing OFSP and 27 percentage points more likely to correctly state the nutritional benefits of OFSP compared to those in control villages. We also find up to 16 percentage point increase in the likelihood of OFSP consumption by children under 5 years of age in treatment villages compared to that in control villages. Furthermore, we find suggestive evidence that increased knowledge on the nutritional benefits of OFSP mediated up to a third of the total treatment effect on OFSP adoption and consumption. Our findings suggest that rural primary schools can be effective channels for promoting and accelerating the diffusion of micronutrient-rich crop varieties in rural areas.